Financial Management Practices, Firm Growth and Profitability of Small and Medium Scale Enterprises (SMEs) - Musah, Alhassan; Gakpetor, Erasmus Dodzi; Pomaa, Portia (Information Management and Business Review, 2018)
The study examined financial management practices using four components: working capital management practices, capital structure management, accounting information and financial reporting practice, and the use of capital budgeting techniques and fixed assets management. Performance of SMEs was examined from the context of profitability measured by Return on Assets and of growth. The study sampled 100 SMEs from Accra with data collected through the administration of a questionnaire. Data were analysed using descriptive statistics and Pearson correlation analysis. The results of the descriptive statistics revealed that working capital management practices had the highest mean score, followed by accounting information and financial reporting practices, capital structure management and finally, the use of capital budgeting techniques and fixed assets management, in that order. The Pearson correlation analysis showed a positive association between the four components of financial management practices and between SMEs profitability and growth. The results emphasize the need for SMEs to improve on their financial management practice to improve the profitability and growth of these firms. It is recommended that the use of capital budgeting techniques be improved, as this area of financial management, even though it impacts positively on the performance of SMEs had the least score. Most importantly, the managers of SMEs should use discounted cash flow techniques to evaluate investment and projects before committing the resources of the company. SMEs are encouraged to adopt IFRS for SMEs to enhance their financial reporting practices. This will also improve their decision making and access to capital which will allow these SMEs to expand.